HYPERTENSIVE PATIENTS WITH ANGINA AND NON-OBSTRUCTIVE CORONARY ARTERY DISEASE ARE CHARACTERIZED BY INCREASED SYMPATHETIC NERVOUS SYSTEM ACTIVATION. (June 2022) - Sakalidis, Athanasios; Dimitriadis, Kyriakos; Dri, Eirini; Soulaidopoulos, Stergios; Mantzouranis, Emmanouil; Manta, Eleni; Aznaouridis, Konstantinos; Vaina, Sophia; Leontsinis, Ioannis; Konstantinou, Konstantinos; Konstantinidis, Dimitris; Tsioufis, Konstantinos
Abstract : Objective: There are data supporting that sympathetic nervous system (SNS) is implicated in the regulation of endothelium function and vascular tone in different cardiovascular disease states. Patients with hypertension and angina frequently present non-obstructive coronary artery disease (CAD) in angiography. The aim of our study was to assess the level of SNS activation in hypertensive patients with angina and non-obstructive CAD, in hypertensives without angina and normotensive controls. Design and method: Our population consisted of 10 treated hypertensive patients with angina who had non-obstructive CAD in coronary angiography [7 females, mean age: 60.5 ± 9.6 years, office blood pressure (BP): 157/93 ± 13/11 mmHg], 16 treated hypertensive patients without angina (9 females, mean age: 59.5 ± 7.5 years, office BP:142/88 mmHg) and 11 normotensive individuals without angina (8 females, mean age: 51.8 ± 11 years, BP:125/87 mmHg). In all participants, muscle sympathetic nerve activity (MSNA) was assessed. Results: Hypertensives with angina and non-obstructive CAD (n = 10) compared to hypertensive patients without angina (n = 16) and normotensives without angina (n = 11) exhibited higher levels of MSNA (57.6 ± 6.1 vs 43 ± 8.4 vs 45 ± 9.5 bursts per minute, respectively; p < 0.01 for all) and 24-h ambulatory BP (144/83 ± 20/14 vs 141/83 ± 7/10 vs to normotensives 125/81 ± 7/6 mmHg, respectively; p < 0.001 for all). There were no differences in renal function between groups and no gender related effects on MSNA values (p = NS). Conclusions: Hypertensive patients with angina and non-obstructive CAD are characterized by higher SNS drive compared to hypertensives without angina and normotensive controls, as reflected by MSNA levels. These preliminary results indicate that therapies targeting SNS tone could be of potential clinical benefit in this high-risk hypertension phenotype.